Active commuting of the inhabitants of Liberec city in low and high walkability areas - Lukáš Rubín; Josef Mitáš; Jan Dygrýn; Jiří Šmída; Lukáš Gábor; Adam Pátek (Palacký University Olomouc, 2015)
Background: Active commuting in terms of everyday transport to school or work can have a significant effect on physical activity. Active commuting can be influenced by the environment, and examples from abroad show that current environmental changes tend mostly to promote passive forms of commuting. A similar situation of decreasing active commuting might be expected in the Czech Republic. However, little information has been published to date about the issue of active commuting among the inhabitants of our country. Objective: The main objective of the present study is to describe the active commuting patterns of the inhabitants of Liberec city in low and high walkability areas. Methods: A total of 23,621 economically active inhabitants or students of Liberec city aged 6-87 years (34.77 ± 14.39) participated in the study. The data about commuting were retrieved from the national Population and Housing Census of 2011. Geographic information systems were used to objectively analyze the built environment and to calculate the walkability index. Results: Active commuting to/from school or work is used by 17.41% of inhabitants. Active commuting is dominated by walking (16.60%) as opposed to cycling (0.81%). Inhabitants who lived in high walkability areas were more likely to actively commute than those living in low walkability areas (OR = 1.54; 95% CI [1.41, 1.68]). Conclusions: This study confirmed the findings of international studies about the effect of the built environment on active commuting among Liberec inhabitants. Active commuters are often those living near or in the city center, which is characterized by high walkability. In Liberec city, walking as a means of active commuting significantly prevails over cycling. One of the reasons might be the diverse topography of the city and the insufficiently developed cycling network.